1995
DOI: 10.1016/0378-1097(95)00047-9
|View full text |Cite
|
Sign up to set email alerts
|

A cytochrome P450-like gene possibly involved in oleandomycin biosynthesis by Streptomyces antibioticus

Abstract: A cosmid clone from an oleandomycin producer, Streptomyces antibioticus, contains a large open reading frame encoding a type I polyketide synthase subunit and an oleandomycin resistance gene (oleB). Sequencing of a 1.4-kb DNA fragment adjacent to oleB revealed the existence of an open reading frame (oleP) encoding a protein similar to several cytochrome P450 monooxygenases from different sources, including the products of the eryF and eryK genes from Saccharopolyspora erythraea that participate in erythromycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 4 publications
0
35
0
Order By: Relevance
“…There are also a number of P450s from different Streptomyces species having about 36% identity, including CYP107C1 from S. thermotolerans (Q60005), CYP107L1 (PikC) from Streptomyces venezuelae (O87605), PTED from Streptomyces avermitilis (Q93H80), and CYP107D1 (OLEP) from Streptomyces antibioticus (Q59819). This last group of related P450s is known to be involved in modification of macrolide antibiotics such as carbomycin (46), methymycin, neomethymycin, pikromycin (19,21,22), novamethymycin (23), avermectin (15), and oleandomycin (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also a number of P450s from different Streptomyces species having about 36% identity, including CYP107C1 from S. thermotolerans (Q60005), CYP107L1 (PikC) from Streptomyces venezuelae (O87605), PTED from Streptomyces avermitilis (Q93H80), and CYP107D1 (OLEP) from Streptomyces antibioticus (Q59819). This last group of related P450s is known to be involved in modification of macrolide antibiotics such as carbomycin (46), methymycin, neomethymycin, pikromycin (19,21,22), novamethymycin (23), avermectin (15), and oleandomycin (24).…”
Section: Resultsmentioning
confidence: 99%
“…The clustering of secondary metabolite genes has been an aid in the isolation of P450 monooxygenases involved in antibiotic biosynthesis. Cytochrome P450 monooxygenases are particularly common in polyketide biosynthetic gene clusters, and they catalyze site-specific tailoring reactions leading to the macrolide antibiotics, including methymycin, neomethymycin, and pikromycin (12, 19 -22), novamethymycin (23), oleandomycin (24), amphotericin (17), and erythromycin (25,26 ally, CYPs are involved in the formation of the anticancer agent epothilone (27,28), immunosuppressant rapamycin (29,30), the growth promoter tylosin (14), and the antiparasitic agent avermectin (15). These reactions typically occur during the late stages of biosynthesis after formation of the core ring system by a polyketide synthase.…”
mentioning
confidence: 99%
“…Comparison of its sequence to four bacterial P450 epoxidases from secondary metabolic pathways (EpoK, PimD, MycG, and OleP) revealed that all share two conserved motifs ( Figure S2). 20,21,23,24,31,32 A Ser or Thr residue in motif-I is likely responsible for O 2 binding and cleavage, and an invariant Cys residue in motif-II presumably serves as the fifth ligand for the heme iron. The presence of these conserved sequence motifs suggested that CrpE is a P450 enzyme.…”
Section: Reconstruction Of P450 Mbp-crpe Reaction Systemmentioning
confidence: 99%
“…[19] Significant homologies were also observed with EthB (34% amino-acid identity), a cytochrome-P450 monooxygenase from Rhodococcus ruber involved in the degradation of ethyl tert-butyl ether (ETBE), [20] and to a number of bacterial cytochrome-P450 enzymes (> 30% amino-acid identity), including oxygenases of macrolide antibiotic biosyntheses pathways, for example, EryF, [21] TylI, [22] PicK (PikC), [23,24] and OleP. [25] All the latter enzymes catalyze the hydroxylation of aliphatic macro-lide structures. EthB is also believed to hydroxylate ETBE to form a hemiacetal intermediate, which spontaneously decomposes into acetaldehyde and tert-butanol.…”
Section: Sequence Analysismentioning
confidence: 99%